2021
DOI: 10.7759/cureus.19065
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Sarcopenia With Modified Frailty Index as a Predictor of Outcome in Critically Ill Elderly Patients: A Cross-Sectional Study

Abstract: Introduction: Frailty phenotype represents weight loss, decreased functional and physical capacity and activity, falls, slow gait, and memory impairment. Sarcopenia is a generalized and progressive loss of skeletal muscle mass, strength, and function, which occurs due to primary effects of aging and secondary effects of other causes including diseases, malnutrition, and inactivity.Materials and Methods: This prospective cross-sectional study was performed on 70 critically ill geriatric patients (of age > 60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…According to the literature, a patient with a score above 4 has a 42% risk of being sarcopenic [33][34][35]. The total score obtained by the patient was 9 points, which pleads for a definite diagnosis of sarcopenia [36,37].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the literature, a patient with a score above 4 has a 42% risk of being sarcopenic [33][34][35]. The total score obtained by the patient was 9 points, which pleads for a definite diagnosis of sarcopenia [36,37].…”
Section: Resultsmentioning
confidence: 92%
“…This suggestion was adopted by EWGSOP [30]. In the case of the patient under investigation, the detected muscle strength was less than 20 kg, which represents the limit value that advocates for one diagnosis of sarcopenia [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…We are not sure if the observed prevalence of malnutrition from the study was a cause or a possible consequence of the observed decline in functional status and the three-month all-cause mortality outcomes at follow-up [ 17 ]. This study has not used other indexes that have been used previously in the elderly, such as the Modified Frailty Index [ 18 ]. However, taking into view the results of the current study, stating that both nutritional and functional status are clinically significant parameters to predict mortality outcomes in the elderly age group, there is a need of further exploration in future studies, especially while formulating for some interventional measures.…”
Section: Discussionmentioning
confidence: 99%
“…One important consideration is the coexistence of sarcopenia in older overweight/obese cancer patients [ 13 ]. Having diminished lean mass compared to fat mass already places these individuals at risk for frailty/disability [ 14 ]. Interventions that focus on weight loss irrespective of the type could potentially lead to further decreases in muscle mass.…”
Section: Discussionmentioning
confidence: 99%